2023
DOI: 10.1029/2022wr034151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bed Roughness on Flow and Turbulence Structure Around a Partially‐Buried, Isolated Freshwater Mussel

Abstract: Freshwater mussels are molluscs that live at the sediment-water interface. They are often encountered in sand and gravel bed rivers that provide more favorable habitat. They play an important role in many fluvial environments by increasing the sustainability of stream ecosystems (Marion et al., 2014). For example, they constitute a fundamental link in many food chains (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Thus, areas that create heterogeneous substrates, such as flow transition areas, may be important for identifying relocation or restoration sites. Furthermore, sediment characteristics can represent flow and turbulence (Lazzarin et al, 2023), both of which are components that structure mussel habitat but are relatively complex features to measure over longer timespans.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…Thus, areas that create heterogeneous substrates, such as flow transition areas, may be important for identifying relocation or restoration sites. Furthermore, sediment characteristics can represent flow and turbulence (Lazzarin et al, 2023), both of which are components that structure mussel habitat but are relatively complex features to measure over longer timespans.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…Eddy-resolving turbulence models such as LES (Constantinescu et al, 2013) and DES (Lazzarin et al, 2023) were used to simulate the flow around mussels. However, compared to the previous study, the individual mussels in this study were significantly smaller and their attachment was much denser, resulting in increased computational requirements.…”
Section: Governing Equationsmentioning
confidence: 99%
“…When the density of Lampsilis siliquoidea exceeded 25 mussels/m 2 on the wall surface, the turbulent shear stresses acting on the mussels were reduced by up to 64% (Sansom et al, 2020). The study of the flow field structure around the mussels revealed that vortex structures were formed around the mussels, which increased the wall shear stress and induced local scour in front and behind the mussel (Lazzarin et al, 2023). In most studies of mussel roughness, the studied species were much larger than LF, thus the pervious findings may be not applicable for LF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations